PERANCANGAN BUKU DIGITAL INTERAKTIF BERBASIS FLIPPING BOOK TIK KELAS XI SMA - Rusdha Aulia; Syaad Patmantara; Anik Nur Handayani (SENTIA 2016, 2016)
Textbook  is  the  main  source  of  study  for  learning  process  Subject  of  Information  and  Communication Technology (ICT) of XI Senior High School. Teacher will explain about textbook content to make student more understand about the concept. Beside that, teacher used slide presentation for boost student perception about practical concept. However, because of limitation sources of study, students often study independently refers to the textbook. It was become an obstacle for students to understand the consept that will be practiced. Interactive digital book design based flipping book can be one of the alternative media that can be used to facilitate the learning process, both in the classroom or used independently. Using the model of Dick and Carey design development, interactive digital book design is easier to be developed with clear steps and goal-oriented. In addition, the product will be designed based on the conditions, needs, and feasibility level is measured both in terms of the material presented, instructional design, display, and aspects of the software development results. This digital book contains of interactive features with full of the concept, combines text, images, audio and video as simulation practice allows students to understand the material presented and more interesting to learn ICT.